2003
DOI: 10.1007/s00439-003-1016-3
|View full text |Cite
|
Sign up to set email alerts
|

Small supernumerary marker chromosomes (SMCs): genotype-phenotype correlation and classification

Abstract: Small supernumerary marker chromosomes (SMCs) are present in about 0.05% of the human population. In approximately 30% of SMC carriers (excluding the approximately 60% SMC derived from one of the acrocentric chromosomes), an abnormal phenotype is observed. The clinical outcome of an SMC is difficult to predict as they can have different phenotypic consequences because of (1). differences in euchromatic DNA-content, (2). different degrees of mosaicism, and/or (3). uniparental disomy (UPD) of the chromosomes hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
151
2
6

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(166 citation statements)
references
References 50 publications
7
151
2
6
Order By: Relevance
“…The first patient had a ring chromosome containing a small amount of euchromatic material, while the second patient was a carrier of a small metacentric and most probably heterochromatic marker. A similar case was reported by Cotter et al (25), with a karyotype of 47,XY,+mar [3]/46,XY [17] reported to be phenotypically normal at birth. The fourth case of a prenatally detected 46,XY/47,XY,+r(20)/47,XY,+20, showed delayed psychomotor development, physical anomalies and growth retardation at the age of 16 months (26).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The first patient had a ring chromosome containing a small amount of euchromatic material, while the second patient was a carrier of a small metacentric and most probably heterochromatic marker. A similar case was reported by Cotter et al (25), with a karyotype of 47,XY,+mar [3]/46,XY [17] reported to be phenotypically normal at birth. The fourth case of a prenatally detected 46,XY/47,XY,+r(20)/47,XY,+20, showed delayed psychomotor development, physical anomalies and growth retardation at the age of 16 months (26).…”
Section: Discussionsupporting
confidence: 81%
“…These chromosomes are detected in 0.04% of newborn children, whereas in developmentally retarded patients the rate is 0.22% (1)(2)(3). sSMCs are also present in 0.08% of unselected pre-natal cases and in 0.20% of pre-natal cases with ultrasound abnormalities (2).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the detailed review of Crolla, 10 so far only one large-scale study of the euchromatic DNA content in pre-and postnatal SMCs has been reported. 7 Frequencies of the different SMCs Our study shows a prevalence of 1/1032 (n ¼ 42) for SMCs at prenatal diagnosis, 1/1492 for de novo SMCs (n ¼ 29), and 1/3328 for the familial SMCs (n ¼ 13). Previous studies reported SMC frequencies of 0.4/1000, 3 0.8/1000, 21 1/1000, 5 and 1.5/1000.…”
Section: Discussionmentioning
confidence: 67%
“…7,11,17 The stepwise investigation of minute SMCs (classes III and IV) included (i) the identification of the a-satellite suprachromosomal family by low-stringency hybridization allowing cross-hybridization between members of the same suprafamily, 13 (ii) the identification of the chromosomal origin by highstringency (chromosome-specific) hybridization of alphoid DNA probes, and (iii) analysis of the euchromatin DNA content using region-specific probes such as BACs. 7,11 There have been attempts to detect the euchromatin on SMCs by using of whole chromosome painting, 16 but due to the presence of centromeric DNA in some paints, this approach is artifact prone: heterochromatic and euchromatic SMCs (classes I vs II or classes III vs IV) may be confused. This study has shown that the stepwise procedure is effective and fast; final results were obtained (usually within 1 week) for 92.3% (12 of 13) of the minute SMCs.…”
Section: Fish Strategymentioning
confidence: 99%
See 1 more Smart Citation